The Effect of Glycine Supplementation on Performance of Broilers Fed Sub-marginal Protein with Adequate Synthetic Methionine and Lysine - Sohail, S.S.; Bryant, M.M.; Roland Sr., D.A. (International Journal of Poultry Science, 2003)
A study was conducted to determine if synthetic glycine could replace dietary protein and improve performance of commercial broilers. Nine diets were formulated per feed regimen (starter, finisher, and withdrawal). A commercial diet was used as control (Diet A). Amino acids were reduced by 15% from Diet A to obtain Diet B. Synthetic methionine and lysine were added to Diet B to bring their level equal to Diet A, and create Diet C. Three levels of synthetic glycine (0, 0.05 and 0.1%) were added to Diets A, B, and C to obtain the nine dietary treatments. Male chicks (n = 3,150) originating from Ross male x Hubbard female breeder flocks were randomly placed in 63 floor pens in an open-sided house with thermostatically controlled curtains. Floor pens were divided into 7 blocks, each block containing 9 pens. The nine dietary treatments in each feed regimen were randomly assigned to pens in each of the seven blocks on d 1 (starter), 22 (finisher), and 43 (withdrawal) of age. Mortality, feed consumption (FC), body weight (BW) and feed to gain ratio (FG) were determined. Supplementing glycine, or methionine and lysine had no effect on FC. Glycine had no influence on the BW of chicks. The BW decreased with the reduction in dietary amino acids, and increased with an increase in dietary methionine and lysine fed the amino acid deficient diet. Glycine had no beneficial effect on FG, and 0.05% glycine increased (P < 0.05) FG up to 3 weeks. Addition of synthetic glycine (0.05 to 0.1%) to the 15% amino acid deficient diet could not make up for the deficiency of dietary amino acids in broiler diets.